Synthesis of mesoporous MgO single crystals without templates - Veldurthi, Shashikala; Shin, Chae-Ho; Joo, Oh-Shim; Jung, Kwang-Deog (ELSEVIER, 2012)
Single crystals of MgO were synthesized using a simple precipitation method with no templates. The magnesium hydroxide was synthesized at 25 degrees C or 100 degrees C by the precipitation of magnesium nitrate solution, aged at room temperature or 100 degrees C. Precipitation temperature had a great influence on the morphology in the synthesis of magnesium oxide. The N-2 physisorption, XRD and electron microscopic (SEM/TEM, HRTEM) analysis associated with the electron diffraction reveal the different morphological structures and pores of MgO synthesized with different synthesis methods. Precipitation at 25 degrees C generated macroporous MgO with plate-like crystals. However, the change of precipitation temperature to 100 degrees C generated mesoporous single crystalline MgO, and the stabilization and growth of MgO(111) planes (with d-spacing of 0.244 nm) was observed. The formation of mesopores and single crystallinity of MgO synthesized by the precipitation at 100 degrees C were retained even after calcination at a temperature of 800 degrees C for 5 h. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: MAGNESIUM-OXIDE; NUCLEATION; GROWTH